Features of decorative art in the Stavropol region - Kalabuhova E. V. (Interactive science, 2016)
the article considers the specifics of the decorative arts in the Stavropol region. The creative efforts of artists and arts collectives of the enterprises – folk traditions continue to evolve in a new form in modern products. Today the art and crafts presented by such products as Kislovodsk porcelain, rugs, carpets, embroidery, Souvenirs. A reflection of the continuous creative search and new discoveries of artist was the technique of enamel.
Keywords: декоративно-прикладное искусство; народные промыслы; кисловодский фарфор; пятигорские ковры; народные умельцы; эмальерное искусство; decorative arts; folk crafts; porcelain Kislovodsk; Pyatigorsk carpets; craftsmen; enamel art